SISTEM INFORMASI PENGADAAN BARANG LANGSUNG BERBASIS CLIENT-SERVER (Study Kasus di Universitas Mataram) - Musta’an Musta’an; Dadang Priyanto (Universitas Bumigora, 2016)
Te procurement of infrastructure for Faculty of Engineering, University of Mataram was conducted through the direct of purchasing, but the process as such ofen remain the administrative obstacle in the process. To avoid the intricate troubles, such as; the number of packets, limited resources, and time issued during the process as well, needed the client server-based information system rather than the computerization manually. Te method implemented was the waterfall for information, and the result was the system of direct purchasing with the client server-based that implemented on Java Netbeasn 8.0 and PostgreSQL 9.0 using Model View Control (MVC) concept for diminishing the false.